Korelasi Diversitas dan Densitas Fitoplankton Terhadap Konsentrasi Nutrien dan Kadmium di Kolam Pengolahan Lindi TPST Piyungan, Bantul, Daerah Istimewa Yogyakarta - , AFINA DINA KAMILA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Secondary effluent of leachate treatment pond of Piyungan landfill is still containing highly nutrients that can conduct to eutrophication. Bioremediation can be done to solve this problem using phytoplankton which can adapt well and has capability of remediation. Some genera have been found in leachate treatment pond of TPST Piyungan, but there is no information about their capability of remediation. This study discussed the diversity and density of phytoplankton in leachate treatment ponds. Furthermore, the physical-chemical parameters were measured. This study was conducted in Leachate Treatment Pond TPST Piyungan. Samples were taken from three ponds using plankton net 100 mesh filtration. Phytoplanktons were enumerated in SRCC. Concentrations of total N, total P and Cd of each pond were measured. The result showed there were eight genera found in leachate treatment pond of TPST Piyungan. Shannon-Wienner index of each pond was 1.226, 0.235, 0.003, respectively. This result showed that phytoplankton in leachate treatment pond of TPST Piyungan had very low diversity and high density. This study reported that Chlamydomonas could be found in eutrophic environment and experienced bloom since their ability to accumulate Cd and survived in low oxygen condition. Total density of phytoplankton had negative correlation with total N and total P concentration but had no correlation with Cd concentration.